High mortality from Plasmodium falciparum malaria in children living with sickle cell anemia on the coast of Kenya. - McAuley, C; Webb, C; Makani, J; Macharia, A; Uyoga, S; Opi, D; Ndila, C; Ngatia, A; Scott, J; Marsh, K; Williams, T (2010)
Although malaria is widely considered a major cause of death in young children born with sickle cell anemia (SCA) in sub-Saharan Africa, this is poorly quantified. We attempted to investigate this question through 4 large case-control analyses involving 7164 children living on the coast of Kenya. SCA was associated with an increased risk of admission to hospital both with nonmalaria diseases in general (odds ratio [OR] = 4.17; 95% confidence interval [CI], 1.95-8.92; P < .001) and with invasive bacterial diseases in particular (OR = 8.73; 95% CI, 4.51-16.89; P < .001). We found no evidence for a strongly increased risk of either uncomplicated malaria (OR = 0.43; 95% CI, 0.09-2.10; P = .30) or malaria complicated by a range of well-described clinical features of severity (OR = 0.80; 95% CI, 0.25-2.51; P = .70) overall; nevertheless, mortality was considerably higher among SCA than non-SCA children hospitalized with malaria. Our findings highlight both the central role that malaria plays in the high early mortality seen in African children with SCA and the urgent need for better quantitative data. Meanwhile, our study confirms the importance of providing all children living with SCA in malaria-endemic areas with effective prophylaxis.